Acidic-enzymatic co-treatment of food waste for high sugar recovery and biogas production - Aldaas, Aseel; Alam, Md. Zahangir; Azmi, Azlin Suhaida (Penerbit UTM Press, 2024)
Food-waste (FW) has a high content of fermentable sugar which can be exploited to generate an alternative source of fuel that could replace fossil fuels. Anaerobic digestion (AD) is an approach to convert organic-waste into high-value products like biomethane and hydrogen. However, hydrolysis is deemed to be a rate-limiting process in the AD process, limiting biogas production. This study seeks to improve the hydrolysis process through pre-treating FW with chemical and biological treatments. We show that the enzymatic treatment substantially improved the hydrolyzation and solubilization of food waste, resulting in a three folds increase in biogas production compared to untreated food waste. A co-treatment of biological and enzymatic treatments significantly improved the hydrolysis process, solids reduction, and solubilization of the substrate. The soluble chemical oxygen demand (SCOD) and reducing sugar were increased by 50% and 25% respectively, compared to enzymatically treated only. However, the inhibitory effect of accumulated salts from the treatment has limited the application of anaerobic digestion. Our results reveal that using enzymatic and acidic pre-treatment can significantly enhance hydrolysis of FW to increase biogas production, highlighting the potential of AD